Is Culture Important to the Relationship Between Quality of Life and Resilience? Global Implications for Preparing Communities for Environmental and Health Disasters - Skevington, Suzanne M.; , The WHOQOL SRPB Group; Bartos, M.; Bonicato, S.; Fleck, M.; Fang,; Kamel, M.; Chandra, P.; Bisht, D.; Amir, M.; Brambilla, L.; Tazaki, M.; et al. (Frontiers in Psychology, 2020)
Background: Using a preventative approach, we investigated whether international subjective qualities of life (QoL) are associated with resilience to adversity when culture is taken into account. Although resilience has been previously associated with good QoL, cross-cultural studies are scarce. Method: Sequential linear multiple regression models of WHOQOL SRPB data from 15 countries world-wide (N=3019), examined which qualities are most closely associated with resilience, when adjusting for culture and selected demographics. We also examined whether all cultures confirmed this positive association. Of 13 QoL facets identified from a literature summary, seven were associated with defining resilience and six reflected strategies for building resilience; these were tested together. Principle components analysis provided a dependent variable for resilience covering inner strength and hope. Results: The final model explained 52% of resilience overall, of which QoL explained 37%, and culture 12% (p<.0001). Being older than 45 years was a significant covariate. Spiritual QoL from meaning in life, awe and wonder, wholeness and integration, and being kind to others, was linked with strategies for building resilience (28%). Better psychological QoL from high levels of positive feelings and low negative feelings was associated with defining resilience (9%). Larger significant positive β’s were found for 10 cultures, so model “universality” was not confirmed. Conclusions: A new cross-cultural psycho-spiritual model of resilience is presented. Assessing individual QoL profiles could identify suitable community members to build resilience locally in culturally-acceptable styles. WHOQOL SRPB evidence could inform international policy designed to prepare vulnerable cultures threatened with environmental and health disasters. Abstract